2020
DOI: 10.1101/2020.09.08.286955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evolutionarily acquired microRNA shapes development of mammalian cortical projections

Abstract: The corticospinal tract is unique to mammals and the corpus callosum is unique to placental mammals (eutherians). The emergence of these structures is thought to underpin the evolutionary acquisition of complex motor and cognitive skills. Corticospinal motor neurons (CSMN) and callosal projection neurons (CPN) are the archetypal projection neurons of the corticospinal tract and corpus callosum, respectively. Although a number of conserved transcriptional regulators of CSMN and CPN development have been identif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…We have previously shown that miRNAs are differentially expressed by corticospinal vs. callosal projection neurons during their development (17). When we examined the genomic organization of validated corticospinal-enriched miRNAs, we discovered that they mapped to two miRNA clusters: one on mouse chromosome 12, the 12qF1 miRNA cluster (17), and one on mouse chromosome 16, the miR-193b~365 cluster.…”
Section: The Mir-193b~365 Cluster Is Enriched In Corticospinal Projection Neurons and Is Downstream Of The Selector Gene Fezf2mentioning
confidence: 95%
See 4 more Smart Citations
“…We have previously shown that miRNAs are differentially expressed by corticospinal vs. callosal projection neurons during their development (17). When we examined the genomic organization of validated corticospinal-enriched miRNAs, we discovered that they mapped to two miRNA clusters: one on mouse chromosome 12, the 12qF1 miRNA cluster (17), and one on mouse chromosome 16, the miR-193b~365 cluster.…”
Section: The Mir-193b~365 Cluster Is Enriched In Corticospinal Projection Neurons and Is Downstream Of The Selector Gene Fezf2mentioning
confidence: 95%
“…We have previously shown that miRNAs are differentially expressed by corticospinal vs. callosal projection neurons during their development (17). When we examined the genomic organization of validated corticospinal-enriched miRNAs, we discovered that they mapped to two miRNA clusters: one on mouse chromosome 12, the 12qF1 miRNA cluster (17), and one on mouse chromosome 16, the miR-193b~365 cluster. We purified independent samples of corticospinal and callosal projection neurons in biological triplicate on postnatal day two (P2), and compared the Relative Quantity (RQ) of miRNA in corticospinal relative to callosal projection neurons, calculated as 2 -DDCt .…”
Section: The Mir-193b~365 Cluster Is Enriched In Corticospinal Projection Neurons and Is Downstream Of The Selector Gene Fezf2mentioning
confidence: 95%
See 3 more Smart Citations